Correction: Identification of the key structural elements of a dihydropyrimidinone core driving toward more potent Hsp90 C-terminal inhibitors. Issue 92 (2nd November 2016) - Terracciano, S.; Chini, M. G.; Vaccaro, M. C.; Strocchia, M.; Foglia, A.; Vassallo, A.; Saturnino, C.; Riccio, R.; Bifulco, G.; Bruno, I.
Abstract : Correction for 'Identification of the key structural elements of a dihydropyrimidinone core driving toward more potent Hsp90 C-terminal inhibitors' by S. Teracciano et al., Chem. Commun., 2016, 52, 12857–12860.